THE DISTINCTIONS OF THE BEGINNING PRAYING TIME CALCULATION BY RINTO ANUGRAHA - Raizza Kinka Intifada; Ahmad Izzuddin (Al-Hilal: Journal of Islamic Astronomy, 2021)
Praying (Shalat) is a fundamental ritual for moslem. Moslem must have deep understanding about praying time in doing Shalat. In this era, many astronomy and falak scholars make a guideline or formula of an algorithm of the beginning of praying time calculation. One of them is a physic lecturer from Gajah Mada University who concern about calculation, specifically about Islamic astronomy (Falak). He designs algorithm of the beginning of praying time schedule on his book “Mekanika Benda Langit (Celestial Mechanics)” and his personal blog to access the program of the beginning praying time calculation. This work is a kind qualitative research which use library research method. By using descriptive explanatory method, the author will scrutinize factor which differ the calculation of the beginning praying time by Rinto Anugraha that will be compared to the beginning of praying time by Ministry of Religious Affairs of Indonesia. In this study, the authors analyzed that the solar declination data and the equation of time used were calculated manually by looking for initial data from Julian Day. The program presented in the early Rinto Anugraha prayer time algorithm based on modern astronomy is very friendly for the user. In the implication of hisab, Rinto Anugraha uses a constant sun height of -18 ° for the evening prayer time and -20 ° for the dawn prayer time.